THE EFFECT OF ACCOUNTABILITY OF RURAL FUND MANAGEMENT AND INTERNAL CONTROL TO PREVENT CORRUPTION IN VILLAGES OF BOJONGPICUNG DISTRICT - CIANJUR - Dody Faraitody Teguh; Dandi Bahtiar (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2021)
The purpose of this study is to find out the effect of accountability of rural fund management and internal control to prevent corruption in villages at bojongpicung district of Cianjur regency. The objects of the study are village heads, village devices, Village Representative (BPD) and BPD members and community leaders. The sampling criteria are people who understand and are directly involved in the management of the Rural Fund. The sample consisted of 66 people consisting of 11 Village Heads, Village officials, village secretaries, regional executives, technical implementers, BPD and BPD members, as well as community leaders in each village. Then conducted interviews and distributing questionnaires. The results showed that partially Accountability of Rural Fund Management and Internal Control had no effect on Corruption Prevention Efforts, as evidenced by the results of the significance test above 5%. Likewise, the test results simultaneously and together the two variables do not have an effect on the Efforts to Prevent Corruption Crimes, as evidenced by the significance test results above 5%. The basic of theory are the Ministry of Home Affairs Regulation Number 20 of 2018 concerning Rural Financial Management, the Auditing Book (Practical Guidelines for Examination of Accountants by Public Accountants) by Sukrisno Agoes and the Corruption Education Book for Universities published by the Ministry of Education and Culture of the Republic of Indonesia.